Prenatal Poly I:C exposure affects tryptophan-kynurenine metabolism associated with intestinal microbiome in female juvenile rats - Yang, Lirong; Chen, Huiyu; Zeng, Menglu; Lu, Yanfang; Xu, Chen; Cao, Zhenju; Zhong, Fuchun; Yang, Xinyu; Shen, Anying; Su, Yueqing; Deng, Chao; Cao, Hua (Frontiers in Immunology, 2025)
BackgroundEmerging evidence suggests that disrupted tryptophan (TRP) metabolism may contribute to an increased risk of neurodevelopmental disorders (NDDs) in the context of maternal inflammation, with gut microbiota playing a pivotal role in regulating TRP metabolic pathways.MethodsJuvenile female rats prenatally exposed to polyriboinosinic-polyribocytidylic acid (Poly I:C) were used to investigate the association between TRP metabolite disturbance and neuropathological/behavioral abnormalities. Behavioral tests assessed anxiety-like behavior, social interaction, and spatial memory. Immunohistochemical and gene expression analyses were performed on the prefrontal cortex (PFC) to evaluate microglial activation and neuroinflammation. TRP-kynurenine (KYN) pathway activity was measured in both PFC and peripheral circulation, along with intestinal TRP metabolism. Gut microbial composition was analyzed through diversity metrics and specific taxa identification.ResultsPrenatal Poly I:C exposure induced anxiety-like behavior, impaired social interaction, and spatial memory deficits in offspring. The PFC showed sustained microglial activation and chronic neuroinflammation. TRP-KYN pathway activation was observed in both central and peripheral systems, accompanied by significant disruptions in intestinal TRP metabolism. Gut microbial analysis revealed reduced diversity and specific alterations in TRP-related taxa (Ruminococcus gauvreauii_group and Candidatus Saccharimonas). These microbial changes correlated with both intestinal TRP metabolic levels and behavioral abnormalities.ConclusionOur findings demonstrate that aberrant TRP metabolism associated with gut microbiota dysbiosis contributes to neuroinflammation and behavioral deficits in offspring following prenatal immune activation, highlighting the gut-microbiota-TRP axis as a key mechanism in neurodevelopmental impairments.